Physical fitness of female cadets at the military college for sergeants of the National Academy of Land Forces - Andreichuk, V.; Romanchuk , V.; Klymovych , V.; Lototskyi , I.; Pylypchak , I.; Romaniv , I. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. The article presents the results of the obtained data on the level of physical fitness of future sergeant-commanders of branches of the Armed Forces of Ukraine. In the conditions of martial law, when Ukraine has been facing very acute challenges to its national security and territorial integrity for almost two years due to the full- scale invasion and aggressive policy of the Russian Federation, the problem of training military personnel capable of meeting these challenges becomes important. In addition to professional training, physical preparedness is a key factor in achieving this goal in any military specialty. The purpose of the study is to investigate the level of physical preparedness of female cadets of the NCO College of National Army Academy of various specialties for military service. Research material and methods. The research was conducted on the basis of the NCO College of National Army Academy. 129 female cadets of the I-II years of study took part in the study. To achieve the goal, the following research methods were used: theoretical analysis and generalization of scientific and methodical literature; pedagogical testing and methods of mathematical statistics. The testing was carried out according to well-known exercises, which are provided by the Instruction on physical training in the Armed Forces of Ukraine (IFT-2021) and characterize the level of general physical fitness, namely: 100 m run, complex strength exercise and 3 km run. The results. In the course of the study, the results of the physical fitness of female cadets of the NCO College of various specialties were determined. We observe that there is no significant difference between the indicators of the three specialties. The three most common specialties were taken into account, namely: combat specialty – military management (mechanized units – branch commanders of assault units); specialties of support forces – weapons and military equipment (operation); rear specialties – provision of troops (forces). Conclusions. The analysis of indicators among female cadets at the final exams in the 100 m race revealed that the average result was – 17.27±0.4 s; in the complex strength exercise, the result was 59.06±0.9 times, and in the 3 km run, the time was 1054.7±14.9 s (17 min 34.7 s). In our opinion and according to the requirements of the IFT- 2021, the results are insufficient and need improvement (in particular, for cadets of mechanized units and support forces specialties).